Noninvasive prenatal detection and selective analysis of cell-free DNA obtained from maternal blood: evaluation for trisomy 21 and trisomy 18 - Sparks, Andrew B.; Struble, Craig A.; Wang, Eric T.; Song, Ken; Oliphant, Arnold (American journal of obstetrics and gynecology, 2012)
We sought to develop a novel biochemical assay and algorithm for the prenatal evaluation of risk for fetal trisomy 21 (T21) and trisomy 18 (T18) using cell-free DNA obtained from maternal blood. We assayed cell-free DNA from a training set and a blinded validation set of pregnant women, comprising 250 disomy, 72 T21, and 16 T18 pregnancies. We used digital analysis of selected regions in combination with a novel algorithm, fetal-fraction optimized risk of trisomy evaluation (FORTE), to determine trisomy risk for each subject. In all, 163/171 subjects in the training set passed quality control criteria. Using a Z statistic, 35/35 T21 cases and 7/7 T18 cases had Z statistic >3 and 120/121 disomic cases had Z statistic <3. FORTE produced an individualized trisomy risk score for each subject, and correctly discriminated all T21 and T18 cases from disomic cases. All 167 subjects in the blinded validation set passed quality control and FORTE performance matched that observed in the training set correctly discriminating 36/36 T21 cases and 8/8 T18 cases from 123/123 disomic cases. Digital analysis of selected regions and FORTE enable accurate, scalable noninvasive fetal aneuploidy detection.